2021
DOI: 10.1016/j.jce.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Government ideology and economic freedom

Abstract: This paper tests the widespread belief that right-wing governments tend to promote economic freedom while left-wing ones prefer more control over the economy. Using annual data for 106 countries over the period 1975-2015 and a two-step system GMM estimator, this study shows that right-wing governments are indeed more prone to promote economic freedom and to deregulate the economy. It also finds that this effect seems to be stronger in developing/emerging economies than in more developed countries. Moreover, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…Our results show that economic freedom increases in the presence of right‐wing governments and when countries are democratic or tend to evolve into more democratic regimes. These findings are in line with previous empirical works (Acemoglu et al, 2019; Acemoglu & Robinson, 2006; Castro & Martins, 2021; Rodrik, 2000). In column 2, we test for interactions between the Polity2 regime classification and ideology.…”
Section: Empirical Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that economic freedom increases in the presence of right‐wing governments and when countries are democratic or tend to evolve into more democratic regimes. These findings are in line with previous empirical works (Acemoglu et al, 2019; Acemoglu & Robinson, 2006; Castro & Martins, 2021; Rodrik, 2000). In column 2, we test for interactions between the Polity2 regime classification and ideology.…”
Section: Empirical Analysissupporting
confidence: 93%
“…Besides the type of regimes and their respective ideological orientation, other standard socio‐economic and demographic controllers found in the literature are added to the model to be estimated in the next section (see, for example, Castro & Martins, 2021, and the references therein): The level of income is usually associated with economic freedom; while the causality running from economic freedom to income/growth is reasonably well established (de Haan et al, 2006; de Haan & Sturm, 2000, 2001), the opposite is less clear (Aixalá & Fabro, 2009; Farr et al, 1998; Vega‐Gordillo & Álvarez‐Arce, 2003); we use the log of real gross domestic product per capita ( GDPpc ) obtained from World Development Indicators (WDI) dataset to account for the income effect on economic freedom; we expect GDP per capita to have a positive effect on economic freedom. Trade openness is another economic factor that can affect economic freedom; countries that are more open to trade are expected to be associated with higher levels of economic freedom; to account for this effect we add to the model the variable Openness which is computed as exports plus imports as a percentage of GDP; this was obtained from the WDI. Crises are another factor that has been identified as having a negative effect on economic freedom (de Haan et al, 2009; Murphy & Smith, 2017; Stocker, 2016); a dummy that takes the value of one when a financial crises occur ( FinCrisis ) is used to account for this effect; financial crises are identified following the works by Laeven & Valencia (2018) and Nguyen et al (2020, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, recent empirical studies show that left‐wing governments are associated with larger expenditures, while right‐wing governments spend less, confirming the anecdotal suggestion that claims left‐wing governments are larger in size (Magkonis et al., 2021). Moreover, right‐wing governments are more active in promoting privatisation, economic freedom and deregulation when compared with left‐wing governments (Castro & Martins, 2021). Thus, government ideology can have a profound influence on economic policies that can impact economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, left‐wing governments appeal to the labour base and low‐income voters, and is associated with higher expenditures (Baskaran, 2011). On the other hand, it is suggested that right‐wing governments are more concerned with reducing inflation and appeals more towards capital owners (Cahan et al., 2019; Castro & Martins, 2021). As a result, economic growth is expected to be higher under left‐wing governments as they implement more expansionary fiscal and monetary policies (Potrafke, 2020).…”
Section: Introductionmentioning
confidence: 99%